Delayed help seeking behavior in dementia care: preliminary findings from the Clinical Pathway for Alzheimer's Disease in China (CPAD) study. (3rd July 2015) - Zhao, Mei; Lv, Xiaozhen; Tuerxun, Maimaitirexiati; He, Jincai; Luo, Benyan; Chen, Wei; Wang, Kai; Gu, Ping; Kuang, Weihong; Zhou, Yuying; Qu, Qiumin; He, Jianhua; et al.
ABSTRACT: Background: The prevalence and factors associated with delays in help seeking for people with dementia in China are unknown. Methods: Within 1, 010 consecutively registered participants in the Clinical Pathway for Alzheimer's Disease in China (CPAD) study (NCT01779310), 576 persons with dementia (PWDs) and their informants reported the estimated time from symptom onset to first medical visit seeking diagnosis. Univariate analysis of general linear model was used to examine the potential factors associated with the delayed diagnosis seeking. Results: The median duration from the first noticeable symptom to the first visit seeking diagnosis or treatment was 1.77 years. Individuals with a positive family history of dementia had longer duration ( p = 0.05). Compared with other types of dementia, people with vascular dementia (VaD) were referred for diagnosis earliest, and the sequence for such delays was: VaD < Alzheimer's disease (AD) < frontotemporal dementia (FTD) ( p < 0.001). Subtypes of dementia ( p < 0.001), family history ( p = 0.01), and education level ( p = 0.03) were associated with the increased delay in help seeking. Conclusions: In China, seeking diagnosis for PWDs is delayed for approximately 2 years, even in well-established memory clinics. Clinical features, family history, and less education may impede help seeking in dementia care.